Public Services and the Influence of Community Satisfaction on the Rowokangkung Sub-District Government Lumajang - Aviana, Nira Fitri (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study aims to explain public services and community satisfaction with the government of Rowokangkung Subdistrict. It is part of the government's efforts to improve the quality of public services in line with the times and to meet the standards of ideal government performance. The study uses an empirical juridical approach. In legal research, an empirical juridical approach involves social research on factual phenomena that occur in the field. The data consists of government public services and community satisfaction with the Rowokangkung Subdistrict government in Lumajang Regency, East Java. The data sources are community members who require public services from the subdistrict. Data collection techniques include observation, interviews, and documentations. The researcher is part of the Rowokangkung Subdistrict government and can interact directly with the data sources. Therefore, the data presented is natural and reflects the actual state of public services and community satisfaction in Rowokangkung. The analysis technique used is descriptive. Descriptive analysis is conducted by presenting various public services in detail. The research results show that public services in Rowokangkung Subdistrict are optimized through both internal and external efforts. Internal services include the innovation “Menenti Hari” (Serving gladly until late at night), while external services include “Rumah Bersama” (Shared House) and “Ngopi Bareng” (Coffee Gathering). Based on the findings, internal and external services have different impacts. Internal services do not affect the increase in the Community Satisfaction Index (CSI), as evidenced by a decline in the CSI score. However, external services do contribute to an increase in community satisfaction. These external services are provided in collaboration with external parties, and they are one of the key factors in improving public satisfaction with the subdistrict government.